Association between Physical Activity, Pain and Fatigue in Patients undergoing Chemotherapy Treatment - Filipe Pereira Caetano, Antonio; Jean de Oliveira Toscano, José (O Mundo da Saúde, 2020)
Chemotherapy patients have symptoms of pain and fatigue normally used as a justification for not performing physical activity during treatment. However, the association of these variables has not yet been conclusively performed in the studies. The aim of this study was to verify the association between physical activity, levels of pain and fatigue in chemotherapy patients. This was a quantitative, non-experimental and cross-sectional study. For oncological conditions and levels of physical activity, a semi-structured questionnaire was used; for fatigue the PFS-P was used; for pain, the EORTC-QLQ-C30 was used; and correlations were performed with the R-Spearman test (p<0.05). The sample consisted of 64 patients, of both sexes and without metastasis, with an age range of 31-80 years old. Of these patients, 26.57% practiced physical activity before the disease and 11.18% during chemotherapy. In assessing the pain variable, 30.7% of men and 74.51% of women had this symptom, with average score levels of 33 points. Regarding fatigue, 50% had this symptom, with a greater incidence in the affective dimension (7.99). The correlations between pain (-0.267) and fatigue (-0.265) with physical activity were negative. Thus, pain and fatigue were not related to the physical activity of patients undergoing chemotherapy.